1970
DOI: 10.1002/jcp.1040760212
|View full text |Cite
|
Sign up to set email alerts
|

An apparent discrepancy between the number of colony forming units transplanted and survival of busulphan lethally treated rats

Abstract: Conditions for keeping busulphan lethally treated rats alive by transplantation of bone marrow cells from syngeneic donors are described. After busulphan treatment of the donor rats with a dose which only reduces the colony forming units (CFU's) in the marrow (assayed by the spleen colony technique) to half the normal numbers, a t least 100 times as many cells from these treated donors, compared to untreated rats, are required to produce an equivalent increase in survival of busulphan lethally treated recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1970
1970
1982
1982

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This survival effect might be a manifestation of a busulfan-induced stem cell defect. Dunn and Elson [24] found that rats salvaged from WBI by cells from BU-treated animals survived less well than those given normal cells, even though the two groups had comparable numbers of spleen colonies. However, death may not have been due to hematopoietic failure.…”
Section: Discussionmentioning
confidence: 97%
“…This survival effect might be a manifestation of a busulfan-induced stem cell defect. Dunn and Elson [24] found that rats salvaged from WBI by cells from BU-treated animals survived less well than those given normal cells, even though the two groups had comparable numbers of spleen colonies. However, death may not have been due to hematopoietic failure.…”
Section: Discussionmentioning
confidence: 97%
“…Haemopoietic colonies derived from bone marrow or spleen CFU were ob tained in both the bone marrow and spleen of groups of at least 5 rats treated with 30 mg/kg busulphan and 4 mg/kg aminochlorambucil according to the pre viously reported method [7], The mean number of endogenous colonies/spleen at 8.5 days after aminochlorambucil (corresponding to 8-day colonies) in all the ex periments now reported was less than 0.5. This number increased to 1.2±0.2 co lonies/spleen 12.5 days after aminochlorambucil (corresponding to 12-day colo nies).…”
Section: Methodsmentioning
confidence: 99%
“…The total num ber and histological type of colony in both the spleen and femoral bone marrow were obtained from microscopical analysis of 5-um-thick serial, longitudinal sec tions stained in haemotoxylin and eosin [5,7]. Except for megakaryocytic colonies (where 5 megakaryocytes or more were considered a colony) more than 100 cells were classified as a colony which was considered pure, i.e., consisting of one cell line only, unless it contained more than 10% of another cell type [5,7].…”
Section: Methodsmentioning
confidence: 99%